Models for Predicting Quality of Solar-Dried Shrimp (Penaeus vannamei) during Storage Based on Protein Oxidation - Yuye Fu; Yaqiong Liu; Wenxiu Wang; Ran Suo; Jie Wang (Journal of Food Quality)
The purpose of this study was to explore the correlation between protein oxidation and quality and to study the changes in various indexes of solar-dried shrimp (Penaeus vannamei) stored at 37°C and 20°C through vacuum packing and vacuum packaging with antipressure sterilization. The results showed that ΔE as well as TVB-N and carbonyl contents increased, whereas moisture and free thiol (SH) contents decreased with time. Furthermore, SDS-PAGE and scanning electron microscopy revealed protein degradation and damage of shrimp muscle microstructure during storage. A quality prediction model based on protein oxidation was established according to Arrhenius equation. Verification of shrimp quality prediction models revealed that the relative errors of the models based on SH and carbonyl contents were below 10%, indicating that these protein oxidation parameters can be used for reliable estimation of quality changes in dried shrimp during storage.